2019
DOI: 10.1038/s41524-019-0210-3
|View full text |Cite
|
Sign up to set email alerts
|

A review of oxygen reduction mechanisms for metal-free carbon-based electrocatalysts

Abstract: The sluggish kinetics of Oxygen Reduction Reaction (ORR) at the cathode in proton exchange membrane fuel cells or metal-air batteries requires highly effective and stable electrocatalysts to boost the reaction. The low abundance and high price of Pt-based electrocatalysts hamper the widespread application of proton exchange membrane fuel cells and metal-air batteries. As promising alternatives, metal-free carbon materials, especially upon doping heteroatoms or creating defects demonstrated excellent ORR activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
405
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 577 publications
(419 citation statements)
references
References 116 publications
7
405
0
7
Order By: Relevance
“…As a result, there have been many attempts to search for new ORR catalysts based on earth‐abundant elements such as heteroatom (N, B, P, and S)‐doped carbon materials or metal−nitrogen−carbon (M−N−C) catalysts with nonprecious metals such as Fe and Co . Fe−N−C catalysts have been synthesized and exhibit ORR activity comparable to that of Pt‐based catalysts, and the FeN 4 structure embedded within the carbon basal plane has been proposed as the active site .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, there have been many attempts to search for new ORR catalysts based on earth‐abundant elements such as heteroatom (N, B, P, and S)‐doped carbon materials or metal−nitrogen−carbon (M−N−C) catalysts with nonprecious metals such as Fe and Co . Fe−N−C catalysts have been synthesized and exhibit ORR activity comparable to that of Pt‐based catalysts, and the FeN 4 structure embedded within the carbon basal plane has been proposed as the active site .…”
Section: Introductionmentioning
confidence: 99%
“…Pt‐group metals, especially Pt, are ideal catalysts for various heterogeneous catalysis such as electrochemical HER. These metals are located near the top of the HER volcano plot with favorable Gibbs‐free energy for hydrogen adsorption, thus exhibiting the state‐of‐the‐art high efficiency 9–12. Recent studies have confirmed that the performance of these metals can be optimized by employing strategies such as nanostructuring, defect introduction, or use of single‐atom catalysts 6,13…”
mentioning
confidence: 99%
“…It is widely accepted that doping of N atoms into carbon framework is useful to boost the ORR activity. However, which type of the N‐group that makes the main contribution is still not clearly confirmed . Either pyridinic N or graphitic N was regarded as the active sites, whereas some studies suggested that both graphitic N and pyridinic N were responsible for positive onset potential and high current density .…”
Section: Resultsmentioning
confidence: 99%